A pluripotent stem cell-based model for post-implantation human amniotic sac development - Yue Shao (Nature Portfolio, 2017)
Early in human embryonic development, it is unclear how amniotic sac formation is regulated. Here, the authors use a human pluripotent stem cell-based model, termed the post-implantation amniotic sac embryoid, to recapitulate early embryogenic events of human amniotic sac development.